Membracidae of Gabon: genus Euceropsila Boulard, 1978 (Hemiptera: Auchenorrhyncha), with description of two new species - Tomasi, Filippo; Susini, Antonio; Durante, Antonio (Zootaxa, 2025)
The genus Euceropsila Boulard, 1978 is reported for the first time in Gabon. The species E. primus Boulard, 1978 is recorded, and two new species, E. brevis sp. nov. and E. variabilis sp. nov., are proposed. A list of previously known species and a key to Euceropsila species are added.